Optoelectronic parallel-matching architecture: architecture description, performance estimation, and prototype demonstration - Kagawa, K; Nitta, K; Ogura, Y; Tanida, J; Ichioka, Y (Applied optics (2004), 2001)
We propose an optoelectronic parallel-matching architecture (PMA) that provides powerful processing capabilities in global processing compared with conventional parallel-computing architectures. The PMA is composed of a global processor called a parallel-matching (PM) module and multiple processing elements (PE's). The PM module is implemented by a large-fan-out free-space optical interconnection and a PM smart-pixel array (PM-SPA). In the proposed architecture, by means of the PM module each PE can monitor the other PE's by use of several kinds of global data matching as well as interprocessor communication. Theoretical evaluation of the performance shows that the proposed PMA provides tremendous improvement in global processing. A prototype demonstrator of the PM module is constructed on the basis of state-of-the-art optoelectronic devices and a diffractive optical element. The prototype is assumed for use in a multiple-processor system composed of 4 x 4 PE's that are completely connected through bit-serial optical communication channels. The PM-SPA is emulated by a complex programmable device and a complementary metal-oxide semiconductor photodetector array. On the prototype demonstrator the fundamental operations of the PM module were verified at 15 MHz.